Reconstitution of the trimethylamine oxide reductase regulatory elements of Shewanella oneidensis in Escherichia coli - Gon, Stéphanie; Patte, Jean-Claude; Dos Santos, Jean-Philippe; Méjean, Vincent (Journal of bacteriology, 2002)
Several bacteria can grow by using small organic compounds such as trimethylamine oxide (TMAO) as electron acceptors. In Shewanella species, the TMAO reductase respiratory system is encoded by the torECAD operon. We showed that production of the TMAO reductase of S. oneidensis was induced by TMAO and repressed by oxygen, and we noticed that a three-gene cluster (torSTR) encoding a complex two-component regulatory system was present downstream of the torECAD operon. We introduced the torSTR gene cluster into Escherichia coli and showed that this regulatory gene cluster is involved in TMAO induction of the torE promoter but plays no role in the oxygen control. The TorR response regulator was purified, and gel shift and footprinting experiments revealed that TorR binds to a single region located about 70 bases upstream of the transcription start site of the tor structural operon. By deletion analysis, we confirmed that the TorR operator site is required for induction of the tor structural promoter. As the TMAO regulatory system of S. oneidensis is homologous to that of E. coli, we investigated a possible complementation between the TMAO regulatory components of the two bacteria. Interestingly, TorS(ec), the TMAO sensor of E. coli, was able to transphosphorylate TorR(so), the TMAO response regulator of S. oneidensis.